PENGUKURAN TINGKAT EFEKTIVITAS VACUUM PAN DI PT. X - Kulsum, Kulsum (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2016)
In agro-industrial sector especially in sugar factory like PT. x improvement of manufacturing system is one of an improvement effort that intensively conducted so that later it could responds rapidly to market changes. The company always attempt to improve productivity, one of the way that has been done is implement preventive maintenance. But in fact, the outcome hasn’t reached the expectation yet. This research found that allocated time to do breakdown maintenance is the main problem, so that most of the corrective action focused in this problem. This research used OEE measurement, Six Big Losses calculation analysis, and also cause-effect diagram to look for existing problem and to give proposed improvement for the problem. As the result, the biggest factors affecting the low effectiveness of machine is equipment failure losses so that the proposed improvement action is implementing TPM.